School Curriculum Development Training with Collaborative Coding to Enhance Student Skills and Collaboration: Pelatihan Pengembangan Kurikulum Sekolah dengan Collaborative Coding untuk Meningkatkan Keterampilan dan Kolaborasi Siswa - Muslim, Muhammad Panji; Hadi, Novi Trisman; Theresiawati, Theresiawati; Seta, Henki Bayu; Ernawati, Iin Ernawati (Universitas Lancang Kuning, 2024)
In the Society 5.0 era, information technology skills are increasingly crucial for Vocational High School (SMK) students, particularly those focused on Software Engineering (RPL). This study aims to enhance students' collaborative skills in software project development through training in GIT, a distributed version control system. The training was conducted at SMK Badan Perguruan Indonesia, Bandung, with the primary goal of improving students' abilities to work as a team using GIT. The implementation of the community service program (PkM) consisted of four stages: preparation, training, mentoring, and evaluation. During the preparation stage, the team identified specific needs ofstudents and teachers through discussions with the school. The training stage involved introducing the basic concepts of GIT, hands-on practice, and case studies on its application in real projects. The mentoring stage ensured the smooth implementation ofGIT, followed by evaluation through pre-tests, post-tests, and participant satisfaction surveys.Results showed a significant improvement in both students' and teachers' understanding. The average increase in teachers' understanding reached 16.19%, with the highest improvement of 40% in understanding how GIT works. Additionally, 26.67% of respondents found the training to be very clear, enjoyable, and beneficial. The implications of this program include improved collaboration quality in students' software projects, as reflected in more structured and well-organized project outcomes. The implementation of GIT also contributed to curriculum enhancement, particularly in project-based learning, aligning more closely with the current demands of the technology industry. This training is expected to be continuously implemented to enhance students' competitiveness in meeting the challenges of the information technology sector.